Pengaruh Brand Ambassador NCT Dream dan Brand Awareness Terhadap Minat Beli Produk Snack Tostos Tortilla Chips - Maulayanissa Maulayanissa; Suci Putri Lestari; Nita Fauziah Oktaviani (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This study aims to determine the influence of NCT Dream Brand Ambassador and Brand Awareness simultaneously on Purchase Interest in TosTos Tortilla Chips snack products. The influence of the NCT Dream Brand Ambassador and Brand Awareness partially on buying interest in TosTos Tortilla Chips snack products. The method used in this study is a quantitative method. With a research sample of 100 people as respondents. Sampling uses non-probability, precisely using purposive sampling. And the analysis method used is multiple linear regression analysis. Based on the research results, it shows that the Brand Ambassador is classified as Very Good, Brand Awareness is included in the very good classification and purchase interest is included in the very good classification. The test results show that simultaneously Brand Ambassador and Brand Awareness have a significant effect on purchasing interest. Partially, Brand Ambassadors have a significant influence on purchasing interest, and Brand Awareness has a significant influence on Purchase Interest.